(untitled) (Polish Yearbook of International Law, 2021)
In 1995, Professor Krzysztof Skubiszewski added a Dissenting Opinion to the East Timor Judgment, wherein the ICJ declined jurisdiction in a proceeding started by Portugal against Australia for its having concluded the East Timor Gap treaty with Indonesia, in blatant violation of the East Timorese’s right to self-determination. Ad-hoc Judge Skubiszewski posited that the Court should have accepted jurisdiction and he presented a series of convincing arguments for this proposition. In 2019 the ICJ rendered an Opinion in the Chagos Islands case. The fact that the ICJ accepted jurisdiction in this case demonstrates that an impressive development has taken place since 1995, one whereby many of Professor Skubiszewki’s requests have been implemented. At the same time however, the Chagos Opinion is not fully satisfying as it neglects, to a considerable extent, the human rights issue. This contribution shows that Skubiszewski’s Dissenting Opinion would have provided guidance also for these questions and that it remains as topical today as it was in 1995.